2014
DOI: 10.5001/omj.2014.29
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Characteristics of Type 1 Diabetes Mellitus in Omani Children - Single Center Experience

Abstract: Polyuria, polydipsia and weight loss are the most common presenting symptoms. Family history of type 1 diabetes mellitus is highly prevalent among the studied patients. Diabetic ketoacidosis was found to be less common in Oman compared to other diabetes centers in the Middle East.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
3
17
1
Order By: Relevance
“…The mean blood glucose level observed at the time of DKA presentation was close to what was stated by other studies (32).…”
Section: Discussionsupporting
confidence: 75%
“…The mean blood glucose level observed at the time of DKA presentation was close to what was stated by other studies (32).…”
Section: Discussionsupporting
confidence: 75%
“…Al-Yaarubi et al 1 mentioned that the frequency of diabetic ketoacidosis (DKA) at diagnosis (31%) was higher than that reported in some developed countries. They addressed some factors contributing to it, namely different racial and environmental factors as well as genetic heterogeneity between Asian and Caucasian populations.…”
Section: To the Editormentioning
confidence: 90%
“…First, it is the consequence of the overall worldwide increased incidence of childhood T1DM over the last few decades. 2 Second, though Al-Yaarubi et al 1 did not address other demographic variables in their study like socioeconomic status and parental education, I presume that these factors might influence the frequency of DKA in their studied population as it was found that DKA at diagnosis was associated with lower family income and lower parental education. 3 Third, Al-Yaarubi et al 1 stated that the overall mean age ± SD at diagnosis of T1DM in the studied patients was 6.7 ± 3.7 years (range: 9 months to 14 years).…”
Section: To the Editormentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, patients do not always comply to dietary and therapy advice, and have a poor attitude to exercise. 8,9 The Diabetes Control and Complications Trial (DCCT) showed a good relationship between the degree of metabolic control and diabetes complications. 7 Intensive management of T1DM can be achieved by using multiple daily injections (MDI) of rapid-acting insulin and a once-daily injection of long-acting insulin, which mimics endogenous insulin secretion characterized by continuous basal insulin secretion and meal-related peaks.…”
mentioning
confidence: 99%